Analysis of the Burial Depth Pattern of Shallow Groundwater Based on Wavelet and Hilbert-Huang Transform Methods - Yu, Ping; Qiu, Lanqing; Ma, Huixin; Li, Fawen; Li, Shaofei; Wang, Ai (Journal of Environmental Accounting and Management, 2026)
As the problems of declining shallow groundwater levels becomes more prominent, depletion of water resources and deterioration of water quality are becoming increasingly prominent. To study the dynamic trend of shallow groundwater and its influencing factors, this study used Hilbert-Huang Transform analysis and Wavelet analysis to analyze the multiscale cycle and trend of the burial depth of shallow groundwater in the Jizhou area of Tianjin and evaluated three factors (annual precipitation, exploitation and evaporation) affecting the burial depth of shallow groundwater by multiple regression and gray correlation analysis. The results showed that there were obvious interannual variation cycles in the burial depth series of shallow groundwater in Jizhou; the correlation between the burial depth of shallow groundwater and the amount of extraction is the greatest; the Wavelet transform and HHT methods had good applicability to the analysis of groundwater hydrological time series, which helped to comprehensively understand the dynamic change characteristics of shallow groundwater.